MiR-10b-5p attenuates spinal cord injury and alleviates LPS-induced PC12 cells injury by inhibiting TGF-β1 decay and activating TGF-β1/Smad3 pathway through PTBP1 - Huandong Liu; Chong Liang; Hongfei Liu; Ping Liang; Huilin Cheng (European Journal of Medical Research)
Abstract Spinal cord injury (SCI) is a debilitating condition characterized by significant sensory, motor, and autonomic dysfunctions, leading to severe physical, psychological, and financial burdens. The current therapeutic approaches for SCI show limited effectiveness, highlighting the urgent need for innovative treatments. MicroRNAs (miRNAs) like miR-10b-5p are known to play pivotal roles in gene expression regulation and have been implicated in various neurodegenerative diseases, including SCI. Polypyrimidine tract binding protein 1 (PTBP1) has also been associated with neural injury responses and recovery. This study aims to explore the interaction between miR-10b-5p and PTBP1 in the context of SCI, hypothesizing that miR-10b-5p regulates PTBP1 to influence SCI pathogenesis and recovery using a rat model of SCI and lipopolysaccharide (LPS)-induced PC12 cells. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was performed to measure miR-10b-5p levels, revealing its low expression in SCI rats. We then assessed neurological function, histopathological changes, and spinal cord water content. We found that administering the agomiR-10b-5p significantly improved neurological function and decreased the spinal cord water content and normal motor neuron loss in SCI rats. Additionally, we explored the functions of miR-10b-5p in LPS-treated PC12 cells. Our results showed that miR-10b-5p repressed LPS-stimulated apoptosis, inflammation, and oxidative stress in PC12 cells. PTBP1 was predicted as a potential target gene of miR-10b-5p using the TargetScan database. Pulldown and luciferase reporter assays further demonstrated that miR-10b-5p binds to the 3’ untranslated region (UTR) of PTBP1. RT-qPCR revealed that miR-10b-5p negatively modulated PTBP1 expression both in vivo and in vitro. Furthermore, rescue assays indicated that miR-10b-5p alleviated SCI in rats and LPS-triggered injury in PC12 cells by downregulating PTBP1. We also investigated the regulation of miR-10b-5p and PTBP1 on the transforming growth factor-beta 1 (TGF-β1)/small mother against decapentaplegic (Smad3) pathway. We found that miR-10b-5p targeted PTBP1 to repress TGF-β1 decay and facilitated TGF-β1/Smad3 pathway activation. In conclusion, our results demonstrate that miR-10b-5p alleviates SCI by repressing TGF-β1 decay and inducing TGF-β1/Smad3 pathway activation through PTBP1 downregulation. This study provides novel insights into potential targeted therapy plans for SCI.